CHARACTERISTICS OF THE INFLUENCE OF CLIMATE CONDITIONS IN THE DESIGN OF BUILDINGS AND CONSTRUCTIONS - Abduraxmonov Abduholiq Abduhodi ogli (Journals Park Publishing, 2022)
The article examines the features of the influence of climatic conditions on the design of buildings and structures. The author comes to the conclusion that, knowing the characteristics of the state of the environment of the future area or structure and having various recommendations for its improvement, architects can more objectively and professionally fulfill their tasks, taking into account possible contradictions, due to spatial solutions using modern technical means, which will lead to the emergence of new architectural forms, original planning techniques. The methods of architectural design, applied taking into account natural and climatic conditions, will enhance the focus of the search for optimal design solutions, as well as enrich the possibilities of architectural creativity.
Keywords: climatic conditions, architectural design, buildings and structures.